Using Procedural And Conceptual Colour Stimulation-Game As an Instructional Gizmo For Nigerian Students - Odewumi Michael Olubunmi (Bina Nusantara University, 2018)
This research study focused on investigating on the effect of colour stimulation-game on Nigerian Junior secondary school creative arts by adopting quasi-experimental research design with 60 junior secondary schools of three co-educational, from Private, Public and Federal Secondary Schools using simple random sampling technique to randomly select The three secondary schools assigned to both experimental and control groups. With the aid of two instruments which were The Colour Stimulation-game and Colour Stimulation-Game Achievement Test (CSGAT), the data was collected. Frequency counts and percentage distribution, mean, standard deviation, independent t-test, ANOVA and ANCOVA were used to analyse the data demographic information, the research question and the hypothesis generated respectively. The researcher found out that the students taught with Stimulus perform better after treatment than the student taught with conventional teaching method, students taught with Colour Stimulus game performed better when exposed to treatment than their students taught with conventional teaching method and female students taught with Colour Stimulus game performed better than their male students. It was recommended that that creative arts instructors should utilizes, colour stimuli game and reducing conventional method do as to impact the appropriates knowledge for studentsKeywords: Colour Stimulation-Game, Colour, Game and instruction, Game, Significant in games